2013
DOI: 10.1002/zamm.201200130
|View full text |Cite
|
Sign up to set email alerts
|

Analytical length scale calibration of nonlocal continuum from a microstructured buckling model

Abstract: International audienceThis paper deals with the buckling of a column which ismodeled by some finite rigid segments and elastic rotational springs and relating its solution to continuum nonlocal elasticity. This problem, which can be referred to Hencky's chain, can serve as a basic model to rigorously investigate the effect of the microstructure on the buckling behaviour of a simple equivalent continuum structural model. The buckling problem of the pinned-pinned discretized column is analytically investigated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…It is worth mentioning that the spatial chaotic behavior of discrete chains has been also observed for non-conservative systems by Kocsis and Károlyi [12]. More recently, Wang et al [13] or Challamel et al [14,15] showed the possibility of linking the linearized Hencky system to non-local mechanics. Non-local mechanics is understood herein as an Eringen's type non-local differential model [16] where an implicit differential equation is assumed between the stress and the strain (or the bending moment and the curvature at the beam scale).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…It is worth mentioning that the spatial chaotic behavior of discrete chains has been also observed for non-conservative systems by Kocsis and Károlyi [12]. More recently, Wang et al [13] or Challamel et al [14,15] showed the possibility of linking the linearized Hencky system to non-local mechanics. Non-local mechanics is understood herein as an Eringen's type non-local differential model [16] where an implicit differential equation is assumed between the stress and the strain (or the bending moment and the curvature at the beam scale).…”
Section: Introductionmentioning
confidence: 86%
“…The analytical solution for the fundamental buckling load issued of the linearization process, has been calculated by Wang [4,5] -see also [11] or more recently by Challamel et al [14,15]. The reasoning is repeated here for completeness.…”
Section: Discrete Elasticamentioning
confidence: 98%
“…Based on the Eringen's nonlocal model, Reddy (2007) studied the bending, buckling and vibration of different linear beam models. Challamel et al (2014) presented an analytical method to calibrate the nonlocal parameter for buckling analysis of micro-structures. However, it was reported that the capability of nonlocal elasticity theory provided to study the size-dependent effects on the mechanical properties of small-scaled structures may exist some limited problems (Eltaher, Hamed, Sadoun, & Mansour, 2014;Li, Yao, Chen, & Li, 2015a;Lim, Zhang, & Reddy, 2015;Ma, Gao, & Reddy, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The basic property of the nonlocal functions can be seen in Lim et al [52]. Some studies [66][67][68][69][70][71] have been presented to identify and incorporate the nonlocal parameter e 0 a for different small-scaled structures. It is worth mentioning that, different materials produce different values of the material characteristic parameter l, some studies [53,72,73] have studied the material characteristic parameter l for different materials.…”
Section: Nonlocal Strain Gradient Theorymentioning
confidence: 98%